Adsorption of phenanthrene by earthworms - A pathway for understanding the fate of hydrophobic organic contaminants in soil-earthworm systems. (15th April 2018) - Shi, Zhiming; Zhang, Fangfang; Wang, Congying
Abstract: The fate of hydrophobic organic contaminants (HOCs) in soil-earthworm systems is an important foundation for soil pollution risk assessment and pollution control. Equilibrium partitioning is considered to be the main mechanism by which HOCs enter earthworms and, as such, a mechanistic model has been developed to estimate the earthworm-water partition coefficients ( K w-w ). In the present study, the adsorption of phenanthrene (PHE) by earthworm tissue was investigated to evaluate the validity of the mechanistic models. Results revealed that K w-w derived from the mechanistic model (346.90) was lower than that derived from the sorption experiments (410.76), indicating that apart from lipid fractions, other components in earthworms, such as protein fractions, might also play an important role in the adsorption of HOCs by earthworm. Besides, the difference between the mechanistic model for earthworm and partition-limited model used for plants are few, indicating that uptake and accumulation mechanisms of HOCs by earthworms and plants are highly consistent internally and are, essentially actually identical. It is also suggested that environmental fate of HOCs in soil-soil biota systems is dominated by their high hydrophobicity. Based on these conclusions, an improved mechanistic model for predicting the uptake of organic contaminants by earthworms has been proposed, which needs to be further evaluated. Furthermore, the feasibility of using vermiaccumulation in vermiremediation of soil contaminated by HOCs was discussed. The adsorption of PHE by earthworm sub-organism fractions (pre-clitellum, clitellum and post-clitellum) and tissue fractions (body wall and gut) were also investigated to interpret the distribution pattern of HOCs in earthworms. At the sub-organism level, the adsorption capacity of PHE by different regions of the earthworm followed the order: post-clitellum > clitellum > pre-clitellum, meaning the distribution of PHE along the earthworm contributes not only to their chemical composition but also to the life activity of earthworms such as circular system. At the tissue level, the gut showed greater affinity with PHE than that of the body wall indicating that the distribution of PHE is mainly due to chemical components at the tissue levels. These results might provide additional understanding of the fate of HOCs in soil-earthworm systems. Graphical abstract: Image 1 Highlights: Adsorption of phenanthrene by earthworm whole body, sub-organism and tissue fractions were studied. Mechanistic model underestimates the earthworm-water partition coefficients of phenanthrene. An improved mechanistic model for predicting the sorption of HOCs to earthworm was proposed. Besides lipids, other components, e.g. protein also affect the distribution of HOCs in earthworm.